2005
DOI: 10.1007/s11095-005-5881-4
|View full text |Cite
|
Sign up to set email alerts
|

Skin Localization of Cow’s Milk Proteins Delivered by a New Ready-to-Use Atopy Patch Test

Abstract: The E-patch system allows native beta-lactoglobulin to concentrate in the stratum corneum, in the vicinity of immunological cells, but does not lead to its systemic delivery. Therefore, it is suggested that this delivery system creates ideal conditions for promoting a positive topical response with reduced risk of systemic anaphylactic reactions caused by the native form of the beta-lactoglobulin A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…Perspiration generated under an occlusive chamber dissolves the lyophilised allergen protein loaded on the Viaskin® EDS [57, 58]. Delivered via such EDS, proteins have been demonstrated to accumulate in the stratum corneum, where they efficiently targets immune cells of the superficial skin layer [60] that rapidly migrate to the draining lymph nodes [57]. In murine studies, EPIT using the Viaskin® EDS showed efficacy equivalent to SCIT in preventing allergic airway reactions upon inhalative allergen challenge [57].…”
Section: Discussionmentioning
confidence: 99%
“…Perspiration generated under an occlusive chamber dissolves the lyophilised allergen protein loaded on the Viaskin® EDS [57, 58]. Delivered via such EDS, proteins have been demonstrated to accumulate in the stratum corneum, where they efficiently targets immune cells of the superficial skin layer [60] that rapidly migrate to the draining lymph nodes [57]. In murine studies, EPIT using the Viaskin® EDS showed efficacy equivalent to SCIT in preventing allergic airway reactions upon inhalative allergen challenge [57].…”
Section: Discussionmentioning
confidence: 99%
“…When applied onto intact skin, the EDS preserves its architecture, including the more superficial layers. Experiments with labeled Ags in in vitro transdermal models have shown that this EDS allows native protein to concentrate inside the stratum corneum within the vicinity of immunological cells, without passage through the skin (7).…”
mentioning
confidence: 99%
“…Whole protein, delivered via such a system, has been demonstrated to accumulate in the stratum corneum, from where it diffuses down to immune cells in the viable layers of the epidermis. 46,71,72 Murine studies, designed to test therapeutic efficacy of the Viaskin ® EDS, demonstrated equivalence of EPIT and SCIT 46 as well as EPIT and SLIT 73 in preventing allergic airway reactions upon airway allergen challenge. Moreover, EPIT using the Viaskin ® EDS was also efficient in the treatment of food allergy as measured by prevention of mast cell degranulation upon oral allergen challenge.…”
Section: Epicutaneous Immunotherapy (Epit)mentioning
confidence: 99%